If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -68 = 85 + -6x Reorder the terms: -68 + 11x = 85 + -6x Solving -68 + 11x = 85 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -68 + 11x + 6x = 85 + -6x + 6x Combine like terms: 11x + 6x = 17x -68 + 17x = 85 + -6x + 6x Combine like terms: -6x + 6x = 0 -68 + 17x = 85 + 0 -68 + 17x = 85 Add '68' to each side of the equation. -68 + 68 + 17x = 85 + 68 Combine like terms: -68 + 68 = 0 0 + 17x = 85 + 68 17x = 85 + 68 Combine like terms: 85 + 68 = 153 17x = 153 Divide each side by '17'. x = 9 Simplifying x = 9
| 14-8/w=3w/4-21 | | 96*9=16a | | 6=-4a+3 | | 11y-10y-22=13 | | 96*16=9a | | 5(3x-1)=7x+1 | | 21+22x=35+15x | | -8x+3x=32+36x | | 6(a+3)=8+6a | | 20x-4=64 | | (x+10)(x+10)=11 | | 9a=16*96 | | 20x+90=10x+120 | | 2x+10=50-8x | | 5+5x+1-3x=-4+6x+5-5x | | 60+42+x=180 | | -6/113/4 | | 448x^4-175x^2y^2= | | 42-5x=28-2x | | 15x^2-6x=153 | | 4k-3=7 | | 30+64=4x-6 | | 1.5X-6=50 | | 2-z=-2 | | 31/2x(1-3)^4 | | 8y-2y=60 | | 3x+7=28-2x | | 6(y-1)=2y+8 | | 4/53/8 | | 5x=12x-6x | | 0.25x+0.1y=1.8 | | 1/31/4 |